Development of the awareness, skills, knowledge: General (ASK-G) scale for measuring cultural competence in the general population - Melanie M. Domenech Rodríguez; Alexandra K. Reveles; Kaylee Litson; Christina A. Patterson; Alejandro L. Vázquez (PLoS ONE, 2022)
Measuring cultural competence has been difficult for conceptual and practical reasons. Yet, professional guidelines and stated values call for training to improve cultural competence. To develop a strong evidence-base for training and improving cultural competence, professionals need reliable and valid measures to capture meaningful changes in cultural competence training. We developed a measure for cultural competence that could be used in a general population to measure changes in awareness, knowledge, and skills in interacting with culturally diverse others. We built an 81-item scale with items conceptually categorized into awareness, knowledge, and skills and was presented to an expert panel for feedback. For evaluation, a national panel of 204 adults responded to the new scale and other measures associated with cultural competence. Factor analysis revealed four factors with strong reliabilities: Awareness of Self, Awareness of Others, Proactive Skills Development, and Knowledge (as = .87 - .92). The final overall scale, Awareness, Knowledge, Skills—General (ASK-G) had 37 items and strong reliability (a = .94). The ASK-G was then compared to validated scales to provide evidence of concurrent, convergent, and divergent validity. Strong evidence emerged for these. The ASK-G is a promising tool to measure cultural competence in a general population.